Episodic Conceptualisation as Genesis of Pupils’ Alternative Conceptions about Graphs in Kinematics - Mohapatra, J.K.; Parida, B.K. (JOURNAL OF INDIAN EDUCATION, 2018)
In the present study, the possible episodic structures which the pupils are likely to auto-generate while being taught about graphs in kinematics, have been identified. The effects of this episodic conceptualisation on the responses of pupils of Classes X and XII, and practising higher secondary teachers to comprehend problems related to the construction and interpretation of graphs in kinematics have been investigated. We have suggested focused teaching points to be noted while teaching graphs so as to minimise the generation of alternative conceptions.